The widening gender wage gap in the gig economy in China: the impact of digitalisation - Jiachen Han; Mingming Li; Shi Li; Yingying Hu (Humanities & Social Sciences Communications)
Abstract The gig economy, fundamentally relying on the digital economy, is often celebrated for its potential to expand employment opportunities and close gender wage gaps. However, research on its gender impacts in China, the largest developing country with a rapidly expanding gig sector, is notably lacking. Employing discrimination theory, the findings challenge the prevailing optimistic view on the role of the gig economy. Utilising the China Labour Dynamics Survey data from 2014, 2016, and 2018, and applying the Bourguignon, Fournier, and Gurgand model to correct selection bias, this study reveals that, digitalisation has exacerbated gender wage gaps, with the wage growth of female gig workers significantly lagging behind their male counterparts, especially among married and older cohorts. Adopting the Neumark decomposition, the analysis confirms that discrimination largely accounts for this gap. This study uses Generalised Propensity Score Matching as robustness test and concludes with policy recommendations.